Optimising the operational parameters of a spherical steriliser for the treatment of oil palm fresh fruit bunch - Kumaradevan, D.; Chuah, K.H.; Moey, L. K.; Mohan, V.; Wan, W. T. (IOP Publishing, 2015)
The extraction of crude palm oil (CPO) begins with the sterilization of oil palm fresh fruit bunch (FFB) in a pressurized, saturated-steam chamber. Sterilization loosens the palm fruits from the stalks and deactivates the free fatty acid (FFA)-producing enzymes. Operational parameters affecting the quality and yield of CPO from an industrial spherical sterilizer are studied at a palm oil mill. The factors are the ripeness of FFB, the number of days before treatment of FFB, and the number of pressure peaks applied in the sterilization process. The results indicate that the degree of ripeness of FFB is the most important parameter affecting the quality and yield of CPO. Ripeness is graded based on the fruits’ colour and the presence of loose fruits. Over ripe FFB that goes for the sterilization process has higher FFA content in CPO and more oil loss to the condensate chamber. The spontaneous reaction on FFB due to accumulation at the loading ramp also gives rise to higher FFA content. Oil loss to condensate chamber is reduced using a two-peak sterilization technique for over ripe FFB; the peak refers to the pressure level of stream after a flushing and refilling cycle. Overall, the generated solution improves the quality and yield of the palm oil mill.